1985
DOI: 10.1111/j.1476-5381.1985.tb17375.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the stereoselective negative inotropic effects of verapamil enantiomers and their binding to putative calcium channels in human heart

Abstract: Ventricular preparations from patients with mitral disease and hypertrophic obstructive cardiomyopathy (HOCM) were set up to contract isometrically. Ventricular membrane particles were also prepared and putative calcium channels were labelled with [3H]‐nimodipine. Positive staircase was induced by varying the rate of stimulation of isolated strips from 6 min−1 to 120 min−1 in the presence of 6–60 μm (—)‐adrenaline or (—)‐noradrenaline. (—)‐Verapamil 3–5 μm or (+)‐verapamil 20–30 μm reversed the force‐frequency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

1986
1986
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(18 citation statements)
references
References 42 publications
2
16
0
Order By: Relevance
“…Data of Clark et al (1982) support our explanation because the dependence on (-)-pindolol concentration of increases in heart rate and myocardial contractile force is similar in spinal cats. An in vitro observation of Ferry et al (1985) supports the staircase concept in man. They increased the pacing rate of isolated ventricular preparations of man between 12 and 120 contractions per minute and observed a proportional increase in contractile force with pacing frequency.…”
Section: Pindolol and The Human Heartsupporting
confidence: 61%
See 1 more Smart Citation
“…Data of Clark et al (1982) support our explanation because the dependence on (-)-pindolol concentration of increases in heart rate and myocardial contractile force is similar in spinal cats. An in vitro observation of Ferry et al (1985) supports the staircase concept in man. They increased the pacing rate of isolated ventricular preparations of man between 12 and 120 contractions per minute and observed a proportional increase in contractile force with pacing frequency.…”
Section: Pindolol and The Human Heartsupporting
confidence: 61%
“…Membrane particles were prepared as described by Kaumann & Birnbaumer (1974), as validated for human cardiac tissues Ferry et al, 1985;Gille et al, 1985). The protein content was determined by the method of Lowry et al (1951) using bovine serum albumin as a standard.…”
Section: Bindingmentioning
confidence: 99%
“…Since hepatic clearance of (-)-verapamil was much greater than that of( + )-verapamil, then, in rats, the more rapid metabolic rate may serve to reduce the potency ratio in terms of dose. In human tissue the potency ratio of the enantiomers in vivo for prolonging PR interval, in terms of unbound plasma concentration (Echizen et al, 1985), and the negative inotropic potency ratio in vitro (Ferry et al, 1985) have been found to be 4.5 and 8 in favour of (-)-verapamil, respectively. These values correspond almost exactly with the antiarrhythmic and in vitro negative inotropic potency ratios in raised K+ solution, respectively, described here.…”
Section: Discussionmentioning
confidence: 97%
“…To test this hypothesis, we have compared the antiarrhythmic actions of the optical enantiomers of verapamil. The hypothesis predicts an antiarrhythmic potency ratio equal to the calcium antagonist potency ratio in the ventricular myocardium, based on the reported potency difference between the enantiomers for calcium antagonism (Bayer et al, 1975;Nawrath et al, 1981;Ferry et al, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…61). The metabolite has been shown to be active in vivo and an estimate of its intrinsic potency at the Ca 2+ channel places it approximately 5-fold less active (Ferry et al, 1985;Johnson et al, 1991). It circulates at a greater concentration than parent and is slightly less protein-bound in plasma (Yong et al, 1980;Powell et al, 1988), thus it can be estimated that it contributes about a third of the activity of the parent drug.…”
mentioning
confidence: 99%